Identification and biocontrol potentials of entomopathogenic fungi and their endophytic effects against Bemisia tabaci gennadius on tomato, Solanum lycopersicum linn - Sani, Ibrahim (2022)
Tomato, Solanum lycopersicum is a plant-vegetable fruit that is widely grown throughout the world due to its nutritive and health benefit. It is a common and popular vegetable in Malaysia, produced and managed largely by smallholders’ farmers, and provides thousands of employments for the peoples. However, insect pests including whitefly, Bemisia tabaci are the major constraints in tomato productions. The application of chemicals is the most efficient option to protect tomatoes against pests and diseases, despite various adverse effects reported on non-target organisms, including beneficial insects (pollinators), livestock and humans. In recent years, researchers have shown an increasing interest in the possibility of using biological control agents including entomopathogenic fungi (EPF) as an alternative to chemical control measures. In addition to direct application to control insect pests, EPF can colonize plant tissues and grow endophytically, benefiting their host plant without causing any symptoms or negative effects. Entomopathogenic fungi were isolated from soil using the insect bait method with mealworm beetle (Tenebrio molitor) and from infected B. tabaci infesting vegetables. All the isolates were identified based on morphological characterization and molecular identification using Internal Transcribed Spacer (ITS) region. The in vitro entomocidal activity of the three Metarhizium anisopliae isolates was evaluated against B. tabaci at different incubation temperatures (15, 20, 25, and 30⁰C) using a concentration of conidia, 1x107conidia/mL. Meanwhile, the virulence of two isolated fungal species, Cordyceps javanica and Purpureocillium lilacinum were evaluated against B. tabaci under laboratory and glasshouse conditions. Furthermore, the effect of tomato seed treated with EPF on plant growth, mortality, and population of B. tabaci were evaluated using the seed inoculation method. A total of 12 isolates of Entomopathogenic fungi (EPF) were identified out of M. anisopliae (seven isolates) and P. lilacinum (two isolates) found from a soil sample, while species C. javanica (two isolates) and P. lilacinum (one isolate) isolated from infected B. tabaci. The percentage mortality of the three isolates of M. anisopliae (Ma-2b, Ma-9a and Ma-15) tested against B. tabaci with an average mortality rate 36.1% - 97.7% at different temperatures (15, 20, 25, and 30⁰C) at 7 days post-treatment. The isolates Ma-15 caused the highest percentage mortality of 97.7% and analysis of LT50 and LT90 shows an increase in mortality (1.6 and 3.9 days respectively), at 30⁰. Moreover, the experiment conducted with C. javanica and P. lilacinum indicated that each of the isolate significantly (p< 0.05) reduce the population of adults and nymphs B. tabaci under laboratory and glasshouse conditions. Our study also revealed that tomato seed treated with C. javanica and P. lilacinum allowed their recovery 60 days after inoculation (DAI). Both endophytic isolates also reduced the population and adult emergence of B. tabaci compared to control treatment. Findings from this study recommend that locally isolated entomopathogenic fungi have the potential to be developed as biopesticides in the future to control whiteflies on tomato plants. The use of entomopathogenic fungi as one of the elements of Integrated Pest Management (IPM) can reduce dependence on the use of chemical pesticides, being environmentally friendly and turn ensuring food safety.